Penerapan Teknik Bimbingan Individual di Kelas pada Mata kuliah Menulis (Sakubun Enshu) (Universitas Negeri Jakarta, 2016)
Subjects of writing (sakubun) in Japanese Language Education Program UNNES has been conducted by various methods and approaches. At first, the students were given a themeand asked to write essays.Then we tried to apply process approach and project work.The results of these experiments only succeeded in improving writing skills in general terms. But, there are still weaknesses in terms of grammar, vocabulary election and coherence between sentences or paragraphs. Based to this background, I think individually guidance is needed to improve students awareness of element that needed when do the writing. The results of this experiment are improved learning outcomes, reduced mistakes, and students found that this technique has helped them. However, because this method is applied to a large class, its implementation becomes less effective and efficient.